Bahasa Promosi Yang Menarik Dalam Peningkatan Penjualan Di Optik Yogya Kuantan Singingi Riau - Saunir, Ihsan (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2025)
Promotion is an activity carried out by a company with the aim of informing, informing, persuading, and influencing consumers in choosing or buying a product offered by the company ofcourse using the attractive language. This study uses a quantitative approach, this is based on the existing problems, the quantitative approach is very appropriate because it emphasizes the numbers (numerical) which are then processed using statistics. Statistically, the hypothesis proposed by the data in the hypothesis test, it can be concluded that the hypothesis presents the influence of attractive promotional language on increasing sales at Optik Yogya Kuantan Singingi is positive and very strong with a percentage of 80%.